2015
DOI: 10.1097/tp.0000000000000271
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Completion Rates of the Medical Prerenal Transplant Evaluation by Race or Ethnicity and Gender

Abstract: Background A significant number of potential kidney transplant candidates do not complete the required medical evaluation after referral to a transplant program. Methods Factors associated with rate of completion of the renal transplant evaluation were analyzed using a retrospective chart review of patients first seen between October 1, 2009 and September 30, 2010 (n=256). The primary end point was completion in 12 months. Independent variables included socioeconomic, demographic, and medical factors. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 28 publications
4
50
0
1
Order By: Relevance
“…This may not be the only factor, however. Monson et al 53 demonstrated that the rate of KT evaluation completion decreased precipitously as the number of required tests increased. Because the need for more testing often reflects increased disease burden, it is not surprising that a patient with substantial comorbidities has a more complicated evaluation process with a reduced likelihood of acceptance for KT.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be the only factor, however. Monson et al 53 demonstrated that the rate of KT evaluation completion decreased precipitously as the number of required tests increased. Because the need for more testing often reflects increased disease burden, it is not surprising that a patient with substantial comorbidities has a more complicated evaluation process with a reduced likelihood of acceptance for KT.…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies showed that AAs were less likely to complete a kidney transplant evaluation than CAs [4, 5]. Indeed, reduced access to kidney transplantation is the most serious disparity in ESRD because it limits duration and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Inadequate education may particularly impact patients with lower socioeconomic status or members of racial/ethnic minorities, contributing to lower rates of referral and transplant listing [2][3][4][5][6]. In addition, patients may choose to reject high KDPI and PHS increased risk organs that are expected to provide benefit out of fear or incomplete understanding of the relative risk of death on dialysis.…”
Section: Accepted Articlementioning
confidence: 99%